Digitalisasi Sastra Kontemporer Lewat Grafik Novel “Tabi” Karya Marchella FP - Liana, Patricia; Riyanto, Edi Dwi; Afdholy, Nadya (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
The digitization of literature is one of the effects of the postmodern era that cannot be avoided. This literaturebased qualitative research investigates the development of postmodernism in literature, with a primary emphasis on its principles and implications in modern literature. This research aims to find out how postmodernism, especially in the digital era, has an impact on the recognition and sales of modern literary works. Using Marchella FP's novel